Investigation into the effect of materials microstructure and properties on micro-cutting precision - Gherman, A.L. (2018)
For the past decades, one of the major trends in industry has been micro-product manufacturing. Micro-parts are in high demand in many industries, including medical devices, electronics and automotive applications. The challenge in manufacturing micro-products is to achieve excellent surface quality in parts with sub-micron tolerances, whilst also maintaining low production costs. Precision can be established based on parameters such as linear and dynamic stability, as well as process repeatability. In micro-cutting, stability is influenced by variations of operating parameters which are considered constant in regular cutting. Such variations have been found in literature for shear angles and cutting forces as a result of the material anisotropy of single crystals. Models and experimental work for cutting force variation due to crystallographic orientation have been previously developed. However, the effects of the cutting force variation have not been sufficiently understood. The aim of the current research is to improve micro-cutting precision based on crystallographic anisotropy models. This thesis achieves four objectives that contribute to a new understanding of micro-cutting by investigating linear and dynamic stability, and repeatability in single crystal investigations. The first objective of this study has been to provide a better understanding of linear stability based on single crystal analytical models. Tool deflection and slope are modelled for the first time due to their proportionality with the cutting force. It is found that tool deflection varies by a factor of two for some crystallographic directions, negatively influencing the stability of the tool path. Cutting forces are also affected by the variation of tool deflection by a six Newtons difference. By providing this new tool deflection model, linear stability understanding is improved for cutting of single crystal materials. The second objective has been to experimentally validate cutting force variation in single grain cutting, and to provide a comparison with multigrain results. Previous studies have investigated either turning, either orthogonal cutting, but they have not considered the evolution of the tangential and radial components of the cutting force during a 360° workpiece rotation. This is critical in order to assess crystallographic anisotropy effects on stability and material deformation mechanisms. The current research has analysed both cutting force components, which enable new models to be developed. The radial cutting force has been successfully found to validate the force profile in the anisotropic analytical model. The third objective has been the development of new, single grain-specific cutting stability models. Classic stability analysis has been extended to include for the first time the variation of the cutting force and shear angle. The new models generate levels of critical depth of cut which vary widely from classic stability values, by 45% in analytically-based analysis and 70% in empirically-determined values. Based on this new knowledge, recommendations of new stability limits are made for manufacturers, in the direction of improving micro-cutting dynamic stability. The final objective of this research has been to provide a new and comprehensive understanding of material deformation mechanisms, due to single crystal cutting effects on surface quality and repeatability of results. Material phenomena analysis is provided for chip formation, burr and ploughing formation, and dimensional accuracy of machined features. Different chip morphologies are characterised for the first time and correlated with anisotropic models. Based on chip typology, chips can be classified as desirable, acceptable or undesirable in cutting. The results show that for a third of the overall number of chips, the morphology is unsuitable for cutting operations. Burr formation has been identified to occur by a four-peak repeatability, which matches the crystallographic anisotropy repeatability; a correlation between chip and burr generating mechanisms is established for 79% of results. In terms of dimensional accuracy, channel width has been analysed. A four-peak pattern and 1.43 times channel dimension variation is found. The chip, burr and dimensional accuracy findings provide an improved understanding of surface quality parameters and repeatability. Based on these new empirical findings, the manufacturing process parameters can be adjusted for optimal micro-cutting. In summary, the research presented in this thesis has investigated the effects of material microstructure properties on micro-cutting precision by developing new models for linear and dynamic stability. For the first time, the correlation between crystallographic anisotropy and surface quality, dimensional accuracy and repeatability have been assessed. These analyses contribute towards an improved understanding of material microstructure effects on micro-cutting precision, and have enabled the development of recommendations to improve micro-manufacturing results.